2021
DOI: 10.1186/s13023-021-02066-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic and clinical characteristics on the trajectories of health-related quality of life among patients with Fabry disease

Abstract: Background Fabry disease (FD) is an X-linked lysosomal storage disorder characterized by multiorgan dysfunction. Since individuals with FD usually experience progressive clinical disease manifestations, their health-related quality of life (HRQOL) is expected to change over time. However, there is limited longitudinal research examining HRQOL outcomes in individuals with FD. We aimed to: assess longitudinal outcomes in HRQOL in adults with FD; examine the physical- and mental HRQOL trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Regarding the effects of age on QOL, QOL appeared to gradually deteriorate with increasing age (22). This finding is remarkably similar to other studies which have shown a continuing decline in QOL with disease progression over time (9,14,31). Negative changes occurred especially in the domains of physical and social functioning indicating difficulties in physical health and personal relationships (31).…”
Section: Correlates Of Qol In Patients With Fdsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the effects of age on QOL, QOL appeared to gradually deteriorate with increasing age (22). This finding is remarkably similar to other studies which have shown a continuing decline in QOL with disease progression over time (9,14,31). Negative changes occurred especially in the domains of physical and social functioning indicating difficulties in physical health and personal relationships (31).…”
Section: Correlates Of Qol In Patients With Fdsupporting
confidence: 91%
“…This finding is remarkably similar to other studies which have shown a continuing decline in QOL with disease progression over time (9,14,31). Negative changes occurred especially in the domains of physical and social functioning indicating difficulties in physical health and personal relationships (31). It is therefore conceivable, that QOL scores in older patients reflect disease burden, rather than an association of age alone (14,31).…”
Section: Correlates Of Qol In Patients With Fdsupporting
confidence: 89%
See 2 more Smart Citations
“…A fourth study by Sigurdardottir and colleagues found that SF-36 scores remained unchanged over a 7–13-year follow-up in a mixed population of male and female patients receiving ERT or chaperone or neither therapy. However, this study did not assess the effect of therapy on SF-36 score [ 43 ].…”
Section: Resultsmentioning
confidence: 99%